MENINGKATKAN HASIL BELAJAR UNSUR INTRINSIK CERITA FIKSI MENGGUNAKAN PENDEKATAN COOPERATIVE SCRIPT PESERTA DIDIK KELAS V SEKOLAH DASAR - Tika Haryanti, Agustin; Mintohari; Kriswati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to enhance the learning outcomes of V grade students at SDN Dukuh Kupang I/488 Surabaya by implementing a cooperative script approach combined with pop card media. The research method used is Classroom Action Research (CAR), with data collected through tests, interviews, and observations. The average learning outcome recorded in the pre-cycle was 57.57%, which increased to 64.10% in Cycle I. Additionally, Cycle II showed a significant improvement in analyzing intrinsic elements of fictional texts, achieving an average of 80.60%. Thus, it can be concluded that the students' learning outcomes demonstrated a noticeable improvement and met the success criteria.